Stroke work progressively increased until maximal exercise in long distance runners, but plateaued at submaximal exercise in sprinters - Fukuda, T.; Matsumoto, A.; Kurano, M.; Nagahama, H.; Nakajima, T. (The Journal of Physical Fitness and Sports Medicine, 2018)
The possible difference in the pattern of cardiac work and stroke work response during exercise between long-distance runners and sprinters remains unclarified. The present study was conducted to elucidate the difference in these responses during exercise between long-distance runners and sprinters. A total of 11 female college athletes (5 long-distance runners and 6 sprinters) performed incremental bicycle exercise testing with respiratory gas exchange measurement. Cardiac index and stroke volume index were continuously measured during exercise by a thoracic impedance method (Physioflow). Cardiac work index (CWI) and stroke work index (SWI) were calculated as the product of cardiac index and mean blood pressure, and the product of stroke volume index and mean blood pressure, respectively. CWI progressively increased from rest to maximal exercise both in long-distance runners and sprinters. SWI progressively increased until maximal exercise in long-distance runners (at 150W: 89.5 ± 3.3 vs. at maximal exercise: 109.3 ± 6.8 g·m·m-2, p < 0.005), but plateaued at 150W in sprinters (at 150W: 107.9 ± 7.6 vs. at maximal exercise: 109.8 ± 6.7 g·m·m-2, p = N.S.). In conclusion, SWI progressively increased until maximal exercise in long-distance runners, but plateaued at submaximal exercise in sprinters. Judging from SWI response during exercise, long-distance runners might have a superior cardiac function compared to sprinters.